2022
DOI: 10.3389/fvets.2022.958163
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of high milk somatic cell counts in dairy cattle in Chiang Mai, Thailand

Abstract: Mastitis in dairy cattle can lead to significant financial losses due to a reduction in milk yield, the withdrawal period after treatment when milk cannot be sold, and an increase in somatic cell count (SCC) which can reduce the milk's per liter commercial value. Dairy cooperatives point at high-SCC problems as an important factor leading to suboptimal levels of milk quantity and quality. This study aims at describing farm characteristics and milking practices associated with high SCC, identifying risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In farms in Thailand where cows get mastitis, they figured out that it costs about $557 for three months. Out of this, 10.4% was lost because the price of milk went down, and the rest which is 89.6% was because the milk had to be thrown away when they found out a cow had mastitis [ 19 ]. In a big milk farming area in Colombia, a study found out that they were losing more than $800.000 every year because of milk losses.…”
Section: Introductionmentioning
confidence: 99%
“…In farms in Thailand where cows get mastitis, they figured out that it costs about $557 for three months. Out of this, 10.4% was lost because the price of milk went down, and the rest which is 89.6% was because the milk had to be thrown away when they found out a cow had mastitis [ 19 ]. In a big milk farming area in Colombia, a study found out that they were losing more than $800.000 every year because of milk losses.…”
Section: Introductionmentioning
confidence: 99%